Deep phenotyping, including quantitative ciliary beating parameters, and extensive genotyping in primary ciliary dyskinesia. Issue 4 (26th November 2019) - Blanchon, Sylvain; Legendre, Marie; Bottier, Mathieu; Tamalet, Aline; Montantin, Guy; Collot, Nathalie; Faucon, Catherine; Dastot, Florence; Copin, Bruno; Clement, Annick; Filoche, Marcel; Coste, André; et al.
Abstract : Background: Primary ciliary dyskinesia (PCD) is a rare genetic disorder resulting in abnormal ciliary motility/structure, extremely heterogeneous at genetic and ultrastructural levels. We aimed, in light of extensive genotyping, to identify specific and quantitative ciliary beating anomalies, according to the ultrastructural phenotype. Methods: We prospectively included 75 patients with PCD exhibiting the main five ultrastructural phenotypes (n=15/group), screened all corresponding PCD genes and measured quantitative beating parameters by high-speed video-microscopy (HSV). Results: Sixty-eight (91%) patients carried biallelic mutations. Combined outer/inner dynein arms (ODA/IDA) defect induces total ciliary immotility, regardless of the gene involved. ODA defect induces a residual beating with dramatically low ciliary beat frequency (CBF) related to increased recovery stroke and pause durations, especially in case of DNAI1 mutations. IDA defect with microtubular disorganisation induces a low percentage of beating cilia with decreased beating angle and, in case of CCDC39 mutations, a relatively conserved mean CBF with a high maximal CBF. Central complex defect induces nearly normal beating parameters, regardless of the gene involved, and a gyrating motion in a minority of ciliated edges, especially in case of RSPH1 mutations. PCD with normal ultrastructure exhibits heterogeneous HSV values, but mostly an increased CBF with an extremely high maximal CBF. Conclusion: Quantitative HSV analysis in PCD objectives beating anomalies associated with specific ciliary ultrastructures and genotypes. It represents a promising approach to guide the molecular analyses towards the best candidate gene(s) to be analysed or to assess the pathogenicity of the numerous sequence variants identified by next-generation-sequencing.